(untitled) (Damascus University Journal of Historical Studies, 2025)
The aquatic dynamics, including useful machines, is a point of prosperity that benefits the Islamic heritage. The science of tricks is known in its broad sense: it is the ability to manage matters, overcome difficult tasks, and circumvent their work by relying on a set of effective technical machines and devices that are based in their operation on a set of engineering structures and principles. minute. The research deals with a review of some of the techniques of one of the engineers of the science of utilitarian water tricks in the Arabic and Islamic civilization, namely Abu Al-Izz Ismail Al-Razzaz Al-Jazari, and the employment of those techniques in the engineering of Damascene service facilities, as these techniques entered the construction of facilities that relied on water for their work, such as water mills, in addition to creating Engineering techniques and tricks that permanently supplied buildings with clean water, such as machines that raise water and deliver it to places (such as buildings and orchards) that are difficult to supply water to it, due to the level of the water stream being lower than its level, in addition to discussing techniques for providing fresh water to the basins and getting rid of impurities from them after use. Al-Jazari also mastered the innovation Machines and tricks that reflected their aesthetic and functional character were derived from the elements of nature, namely water foggara rushing upward. Thus, Fountain were invented that spewed water in its various forms, creating an atmosphere of entertainment and beauty, and their role in wetting the atmosphere in the place which they were constructed.